Islam, Immigration, and Identity (MDPI - Multidisciplinary Digital Publishing Institute, 2014)
It has been two decades since Samuel P. Huntington, a Harvard political scientist, first published his famous essay, "The Clash of Civilizations?" [1]. In the essay, and later in his book with the same title (minus the question mark) [2], Huntington argues that conflict in the post-Cold War era will be driven largely by irreconcilable cultural and religious differences, particularly in regards to Islam and the West. The conflict between these two civilizations, while not new, is bound to persist in large part because Islam is prone to violence. Much of the global conflict that exists in the modern world, observes Huntington, involves Muslims. It is for this reason that he states so bluntly: "Islam has bloody borders" ([1], p. 35). The "clash of civilizations" thesis did not originate with Huntington. Bernard Lewis, the prominent historian of Islam and orientalist, had already invoked this language in his own scholarship, most notably in his 1990 article for The Atlantic Monthly, "The Roots of Muslim Rage" [3]. In the article, Lewis explores many possible explanations as to why Muslims have so much hatred for the West. He concludes that Muslims are jealous and humiliated due to the superiority of Western civilization. Western secularism and modernism in particular are the objects of Muslim anger and the reason behind the surge in Islamic fundamentalism in recent history. Both Huntington and Lewis invoke the very themes that Edward Said describes as the foundation of Orientalism [4]. Both view the West as superior and enlightened, in contrast to the Muslim world (i.e., the Orient), which they portray as monolithic, violent, backwards, and irrational. Conflict is inevitable in light of such profound differences, insist Huntington and Lewis, and yet both scholars maintain that the real source of this conflict lies within Islam. [...]